#1 eliminate y by equating the two:
2x^2-2x-3 = -x^2-2x-3
Now solve for x, and then you can get y
#2 same thing
#3 again, use the discriminant. We want
kx^2-5x+2 = -3x+4
kx^2-2x-6 = 0
The discriminant is 4+24k
1. Solve the system of equations by elimination.y=2x^2-2x-3 and y=-x^2-2x-3
2.The system of equations y=-5(x+4)^2-4 and y=8x^2+64x+124 has _____ solution(s).
3. Determine the value of k in y=kx^2-5x+2 that will result in the intersection of the line y=-3x+4 with the quadratic at
a) two points (1 mark)
b) one points (1 mark)
c) no point (1 mark)
1 answer